Overexpression of ADAM9 in oral squamous cell carcinoma - Pattaramon Tanasubsinn (2018)
© 2018, Spandidos Publications. All rights reserved. Overexpression of a disintegrin and metalloproteinase 9 (ADAM9) has been shown in various types of cancer. Some studies have reported inconclusive findings regarding chromosomal aberrations in the ADAM9‑containing region and ADAM9 expression in oral cancer. Therefore, in this study, ADAM9 protein expression was determined and compared between oral squamous cell carcinoma (OSCC) and normal oral tissues, and between oral cancer cell lines and human oral keratinocytes (HOKs). In total, 34 OSCC and 10 healthy paraffin‑embedded tissue sections were probed with an anti‑ADAM9 antibody, and the immunohistochemical score was determined by multiplying the percentage of positively stained cells with the intensity score. Four different oral cancer and eight independent HOK cell lines were cultured, and the expression of membrane ADAM9 and active ADAM9 at 84 kDa in these cell lines was assayed by flow cytometry and western blot hybridization, respectively. The results showed that the median immunohistochemical score of ADAM9 expression in OSCC tissues was significantly greater than that in normal tissues (P < 0.001). Furthermore, among OSCC cases, intense staining of ADAM9 expression was detected in well‑differentiated and in moderately‑differentiated OSCC; ADAM9 expression was also correlated with an increased degree of cell differentiation (r=0.557; P=0.001). Expression of membrane ADAM9 was present in 3/4 cancer cell lines. Expression of active ADAM9 varied among all the tested cell lines, but significantly higher ADAM9 expression was present in certain cancer cell lines than those in HOKs (P < 0.05). In summary, ADAM9 expression is enhanced in OSCC and oral cancer cell lines, suggesting its role in the pathogenesis of oral cancer. Similar to the overexpression of ADAM9 in well‑differentiated prostate cancer, high degrees of ADAM9 expression have also been observed in well‑differentiated OSCC.